Innovative Civic Education Strategies in Elementary Schools - Putri, Tri; Rizqia, Maulida (Yayasan Zia Salsabila, 2024)
The development of civic competence at the primary school level is often stuck in rote learning that does not encourage the internalization of the values of rights, obligations, and responsibilities as democratic citizens. This study aims to explore the application of the inquiry approach as an innovative strategy in civic education to improve students' understanding of these basic civic concepts. Using a qualitative research design with a case study approach, data were collected through interviews, observations and document analysis involving teachers and students in one primary school in Kendari City, Indonesia. Data analysis was conducted to identify the main themes that emerged. The results showed that the inquiry approach encouraged students to construct knowledge through reflection, dialog, and contextual exploration. Students were able to connect personal experiences with the concepts of rights, obligations, and responsibilities in a meaningful way, and showed improved critical thinking skills and active participation. This research contributes to strengthening the theory of civic education and provides practical implications in designing learning that is oriented towards democratic values from an early age.